Persepsi Orang Tua terhadap Konten TikTok sebagai Referensi Pemilihan Sekolah Anak - Badrus Shalih; M Naqouib Ashrofun Nashr; Sahrahman (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
The rapid growth of TikTok as a social media platform has transformed information consumption patterns among Indonesian parents selecting schools for their children. This study analyzes parents' perceptions of TikTok content as a reference in school selection decisions through a qualitative phenomenological approach, using in-depth interviews, limited digital observation (netnography), and field notes. Data were collected from 24 parents in Pasuruan who actively use TikTok and have school-age children (6–15 years). Three dominant perception dimensions emerged: (1) cognitive perception, encompassing conditional trust in information credibility and active verification strategies; (2) affective perception, involving emotional responses to school promotional content, including comparative anxiety; and (3) conative perception, manifested in behavioral tendencies in school search processes. This study proposes the Tri-Dimensional Social Media Perception (MPMS-TD) framework, which integrates Theory of Planned Behavior, Uses and Gratifications Theory, and Algorithmic Trust to explain how these three dimensions interact in TikTok-mediated decision-making. The results indicate that TikTok strongly influences the initial school information search stage, but final decisions remain largely shaped by direct experience and peer recommendations. These findings have practical implications for educational institutions formulating digital communication strategies on short-video platforms. The study is limited to one urban district and findings should not be generalized beyond comparable contexts.